WAJAH TRANSPORTASI PERKOTAAN PADA KOTA - KOTA MENUJU KOTA METROPOLITAN (STUDI KASUS: SEMARANG METROPOLITAN) - Ismiyati Ismiyati; Sugiono Soetomo (Jurnal Teknik Sipil, 2017)
This study will describe influence of growth of urban uncontrollably toward outside or which is often referred as by urban sprawl to moda choce. Growth of town into metropolitan area need careful because besides affecting social segregasi also cause not effisient mobility of suburban , because journey become long distance is resident activity still concentration at downtown (core city )  and also  the happening of  integration of  each town  also  will  complicate  arrangement  of urban transportation system Purpose of this research is to identify factors growth of urban uncontrollably toward outside its influence  urban  sprawl  to  moda  choce  with  a  view  to  recommend  handling  of  problems  of transportation at metropolitan area. Approach  method  with  approach  of  spasial  pursuant  to  understanding  of  human  being interaction  with  urban  environment  that  is  by  studying  dynamics  friction  of  resident  in  taking choice suburban residence and its mobility choice that is choice of moda transportation. Method acquirement  of  data  by  using  technique  method  interview  household  by  random  proposional pursuant to strata of sosio-ekonomi at region of suburban. Technique analyse by using analysis of crosstabulation statistic with test of significan to describe factors influencing growth of urban and its influence to moda choice. Result  of from  this research  describe  that  growth of town  toward town  boundary  of  Semarang unegual  and  its  surroundings  its  speed  at  some  district  exist  in  study  region.  As  for  factors influencing growth of town besides aksessibilitas there is social factor in the form of change of life  style  toward  requirement  of  settlement  with  balmy  environment  and  requirement  of transportation. Result of from this study is] expected useful for the day- dream of problems of urban  transportation  by  integrating  between  operation  of  policy  of  settlement  of  settlement environment  and  policy  of  operation  of  transportation  system  at  natural  towns of  metropolitan area.